(untitled) - Seki, Mitsuhiro (Tokyo, Japan, 1994)
Contents: Japan, situated in a corner of East Asia, has steadfastly pursued a course of industrial modernization ever since the country was opened to outside influences about 130 years ago.
Keywords: Industries,Công nghiệp; Japan,Nhật Bản